(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
Any calculation is preceded by the stage of creating a design diagram of a real structure, which would most accurately correspond to real operating conditions. The more optimally the design scheme is drawn up, the less laborious the stages of calculation and design of the corresponding structure will be. There are practically no results of using this approach when calculating building structures. This article attempts to show the possibility and expediency of using the "Search for solutions" (add-on for Microsoft Excel) at the stage of choosing the optimal parameters of the design design schemeAny calculation is preceded by the stage of creating a design diagram of a real structure, which would most closely correspond to real operating conditions. The more optimally the design scheme is drawn up, the less laborious the stages of calculation and design of the corresponding structure will be. If the efficiency criterion is a linear function, and the variables in the constraint system are also linear, then such a problem is a linear programming problem. Of the listed methods of mathematical programming, the most common and developed is linear programming. To illustrate the idea of the proposed approach, a simple statically definable truss on two supports was deliberately chosen. This is done so that the idea of the proposed approach is not lost due to the complexity and cumbersomeness of the calculations. This article shows the possibility and feasibility of using the "Search for solutions" at the stage of choosing the optimal parameters of the design design scheme. After the design scheme has been defined, more powerful conventional means of calculating building structures can be involved for its complete calculation.